KALIMAT KONDISIONAL DALAM BAHASA ARAB - Ali Asrun Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
Conditional sentence is a sentence consists of cause and effect parts or “jawab-syarat” that is included one of certain particle called by adat syarty. There is a certain role in this conditional sentence (kaidah lughowiyah) that puts and arranges this sentence to be complete sentence (Jumlah Mufidhah).Adatusy syarathas an important role in determining roleand answered, that is included determining sentence pattern, the meaning of time and purposed. So in arranging conditional sentence Adatusy syarat must be careful.Adatusy syarat is looked from the agglomeration of word part, so that it can be divided into 2 parts, that are huruf, and the second isim, and generally both of them are mabni.